A identidade profissional dos egressos do curso de pedagogia do campus universitário de Abaetetuba - PA - SILVA, Paula Inês Lobato (2022)
The present work aims to investigate how graduates of the Pedagogy course build their professional teaching identity, in the region of Baixo Tocantins. The study is part of the network of specific themes of teacher training, the constitution of the teacher's professional identity and basic education. The theoretical framework is based on studies by RAYMOND and TARDIFF (2000); TARDIF (2002); GATTI (2014; NÓVOA, 1999; SACRISTÁN, 1999; ROLDÃO, 2005. For data collection, questionnaires were sent via social networks, specifically Whatsapp and Google Forms to graduates of the Pedagogy course, from the Abaetetuba Campus, from the Federal University of Pará. In order to think about the practice of data collection in the field, aimed at investigating specifically the construction of the identity of teachers who work in the Baixo Tocantins Region.